Prevention: management of risk and protective factors - Hankey, Graeme (Henry Stewart Talks, 2008)
Patients with ischaemic stroke are at high risk of recurrent vascular events, One strategy to reduce the risk of recurrent events is controlling causal risk factors, Effective strategies include stopping smoking, lowering blood pressure and blood cholesterol, minimising alcohol and salt consumption and optimizing glycosylated haemoglobin, body weight and physical activity
Archived at 2018/12/10